The Role of Tauke in Fluctuations in Areca Farmers' Income According to an Islamic Economic Perspective - Sugianto, Sugianto; Wargo, Wargo (CV. Zabags Qu Publish, 2023)
The background of this research is to see to what extent the role of tauke in increasing the income of areca nut farmers because we do not yet know a clear picture of whether or not the role of tauke in increasing farmer's income is in accordance with the principles of Islamic economics. In this research the problem is what is the role of tauke in increasing the income of areca nut farmers in Jemantan? Is the role of the tauke in accordance with Islamic economic principles in increasing the income of areca nut farmers in Jemantan? The location of this research was carried out in Jemantan. Talang babat sub-district, Muara Sabak Barat sub-district, Tanjung Jabung Timur district, Jambi province. The approach in this research uses a qualitative approach. The research design used in this research is a case study. Residents in this area generally have their livelihoods in agriculture, plantations and several others. The livelihood of the population in general is farming, gardening, producing areca nut. Tauke areca nut plays a role in increasing the income of areca nut farmers in marketing, providing employment opportunities for areca nut farmers who want to earn wages in processing areca nut at the tauke place, providing a financial and social role when the rainy season occurs when farmers cannot harvest, and acts as a container or market for farmers in opening branches to place strategic purchases of areca nut. Judging from the principles of Islamic economics, the role of tauke in increasing the income of areca nut farmers is based on its role in helping the farmer's economy. Tauke plays a role in increasing the income of areca nut farmers in terms of borrowing money, employment opportunities and tauke acts as a forum or market for farmers in opening branches where they can buy areca nut. strategic in accordance with Islamic law. Therefore, areca nut farmers need the role of tauke in increasing the income of areca nut farmers in order to create prosperity